Peningkatan Hasil Belajar Pecahan sebagai Perbandingan dan Skala dengan Model PBL di Kelas V - fitriani, hayatul; dalais, mursal; ahmad, syafri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
Purpose of this research was to describe plan, implementation, and increase of study resultspiece as ratio and scale with Problem Based Learning in fifth level elementary school. The kind of this research was Action Classroom Research with qualitative approach and quantity approach. Subjects of this research were students from fifth level in elementary scool who consist of 14 male and 9 female and also a teacher. This research was implementation on two cycle. It consist of plan, implementation, observation and reflection. The results of research indicated increase on a) Increase plan of first cycle was 76,79% up to 89,28% in second cycle, b) Implementation of teacher aspect on first cycle was 70% increased up to 90% and implementation of students aspect was 67,5% on first cycle and increased up to 90% on second cycle, c) Study result of students on first cycle was 73,30% and 81,69% on second cycle. The conclusion this research was learning  with Problem Based Learning can increased study results of piece as ratio and scale in fifth level elementary school.  Keywords: study results; piece as ratio and scale; problem based learning.